Enhanced quadratic boost converter based on voltage lift technique for fuel cell powered electric vehicle. (September 2022) - Kumar, Mukkapati Ashok Bhupathi; Krishnasamy, Vijayakumar
Abstract: The proton exchange membrane fuel cells (PEMFC) are inherently low voltage and high current sources. Since high voltage is required for motor drives present in fuel cell-powered electric vehicles (FCEV), power converters are required for the integration of PEMFC into the motor drive system. To address this need, the study presented below describes the development and analysis of the proposed high gain step-up converter as a power electronic interface in FCEV. The proposed converter configuration utilizes the voltage lift technique in conjunction with the quadratic boost converter (QBC). The voltage lift technique uses a pair of diodes and capacitors to enhance the voltage gain and to reduce voltage stress across the power switch. A reduction in the voltage stress allows utilizing a low on-state resistance for the switch resulting in improved efficiency of the converter. In addition, the proposed converter draws a continuous or non-pulsating input current from the fuel cell stack which helps to improve its life cycle as well. The performance of the proposed converter is superior to alike converters in terms of voltage gain, voltage stress and the number of components utilized. The operating principles, steady-state analysis in continuous conduction mode (CCM) and key design parameters are described below to prove the superiority of the proposed converter. Finally, a hardware prototype of 200 W is fabricated and tested to affirm the validity of the theoretical analysis. The proposed converter exhibits an efficiency of 94.02%. Graphical abstract: